Radiographical investigation of the condylar position using three-dimensional imaging (a comparative Iraqi study). Issue 2 (4th March 2023) - Hassan, Nuhad A.; Al-Jaboori, Aseel S. Khazaal; Mahmoud, Sanaa J.; Ali, Maisaa Q.
ABSTRACT: Objective: To investigate the condylar position in an Iraqi sample of patients with temporomandibular joint disorders (TMDs) using cone beam computed tomography. Methods: The study included 20 patients with temporomandibular disorders and 20 healthy patients with normal temporomandibular joints (40 individuals in total). Reference landmarks from the sagittal aspect were used to measure various straight distances between the glenoid fossa and condyle, such as the anterior, posterior, and superior joint spaces. The inclination of the articular eminence was also evaluated. Results: There was a statistically significant difference in inclination in the TMD group when patients were categorized by sex. Males had larger superior space and inclination compared with females. Conclusion: Cone beam computed tomography can offer essential information about variations in the TMD group and can be used as one of the indicators for such variations for good diagnosis and treatment.